Resistivity determination of railway track's subgrade / Anas Ibrahim ... [et al.] - Ibrahim, Anas; Ahmad, Azura; Azuddin Fitri, Muhammad Luqman; Yahaya, Noryani Natasha; Kamarudin, Faizah; Abdullah, Muhammad Sofian (Universiti Teknologi MARA, Pulau Pinang, 2023)
The conventional geotechnical investigation method using borehole drilling and sampling was usually performed for subsurface exploration. However, it is -time-consuming, invasive and requires the closing of railway lanes that disrupts the train service. To avoid this problem, a geophysical method is an alternative that can be proposed to assess the conditions of the soil subgrade under the railway track. Electrical resistivity is one of the geophysical methods that study the nature of the electricity flow in the soil by injecting the electric current into the soil and measuring the generated potential difference. The field investigation was conducted at two different locations using electrical resistivity methods to identify the properties of the soil. Two railway track site locations selected were Pinang Tunggal, Pulau Pinang (KM 23), and Alor Setar, Kedah (250 m from the station in the north direction). ABEM Terrameter LS was used in field work that applied two configurations of an array, the Wenner and Schlumberger arrays, to infer the subsurface soil layer. The results concluded that the apparent resistivity data need to be inverted into an actual resistivity data set using Resistivity 2D Inversion (RES2DINV) software. The analysis found that the soil properties are both classified as soft soil with electrical resistivity values ranging from 0 - 100 Ω-m.